Exploring Scaling Relations for Chemisorption Energies on Transition‐Metal‐Exchanged Zeolites ZSM‐22 and ZSM‐5. Issue 4 (12th January 2016) - Siahrostami, Samira; Falsig, Hanne; Beato, Pablo; Moses, Poul Georg; Nørskov, Jens K.; Studt, Felix
Abstract: Copper exchange on all the different T sites of ZSM‐22 and ZSM‐5 is considered and the chemisorption energies of dioxygen, OH, and O species are studied. We show that for different T sites the adsorption energies vary significantly. The oxygen adsorption energy on copper‐exchanged zeolites is quite similar to those of the most selective catalysts for oxidation reactions, that is, Ag and Au surfaces. The chemisorption energies of oxygen, carbon‐, and nitrogen‐containing species on different transition metals exchanged in ZSM‐22 are also investigated. The study covers three different oxidation states, that is, 1+, 2+, and 3+ for the transition‐metal exchanges. Scaling relations are presented for the corresponding species. Chemisorption of O scales with chemisorption of OH for all three considered exchanges, whereas there are essentially rough correlations for NH2 and N as well as CH3 and C. Abstract : Checking affinity for chemisorption : Scaling relations for the binding energies of different adsorbed species in the transition‐metal‐exchanged zeolites are investigated. Color code: yellow=silicon, red=oxygen, brown=copper, blue=aluminum